2022
DOI: 10.1002/cam4.5472
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐testis gene STK31 is regulated by methylation and promotes the development of pancreatic cancer

Abstract: Backgroud Pancreatic cancer (PC) is a highly invasive malignancy with extremely poor prognosis. STK31 has been identified as a cancer‐testis (CT) gene, but its function in PC has not been elucidated well. Methods The effect of STK31 on cell proliferation, migration and invasion was investigated by in vitro and in vivo experiments and total RNA sequencing and targeted bisulfite sequencing was applied to explore the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…STK31 has been implicated in promoting the progression of pancreatic cancer by enhancing cell proliferation, migration, and invasion. High expression of STK31 is associated with a poor prognosis in pancreatic cancer [44]. Previous studies have reported that PLA2G2F is a major secretory phospholipase A2 (sPLA2) expressed in the epidermis across different species, and its expression increases during epidermal hyperplasia.…”
Section: Rt-qpcr Validation For the Expression Of Pla2g2f Hhip Tnxb A...mentioning
confidence: 99%
“…STK31 has been implicated in promoting the progression of pancreatic cancer by enhancing cell proliferation, migration, and invasion. High expression of STK31 is associated with a poor prognosis in pancreatic cancer [44]. Previous studies have reported that PLA2G2F is a major secretory phospholipase A2 (sPLA2) expressed in the epidermis across different species, and its expression increases during epidermal hyperplasia.…”
Section: Rt-qpcr Validation For the Expression Of Pla2g2f Hhip Tnxb A...mentioning
confidence: 99%
“…STK31, also known as TDRD8, is a serine/threonine kinase that contains STK and Tudor domains. STK31 has been identified as a novel cancer testis antigen and has been shown to play an oncogenic role in various cancers, including colorectal, lung, pancreatic, and gastric (23)(24)(25). In lung cancer, STK31 was reported to induce lung cancer cell proliferation through the Wnt signaling pathway (26).…”
Section: Introductionmentioning
confidence: 99%